ANALISIS RETURN ON EQUITY TERHADAP HARGA SAHAM DI PT. BEKASI ASRI PEMULA, TBK - Silvia Silvia (PARAMETER, 2020)
Analysis of Return on Equity Against Stock Prices at PT. Bekasi Asri Pemula, Tbk. This study aims to find out how Return on Equity (ROE) on Stock Prices. The object of this research is PT. Bekasi Asri Pemula, Tbk for the period 2014 - 2017. This study used a qualitative method consisting of two variables, namely Return On Equity (ROE) as an independent variable and stock price as the dependent variable. The data analysis technique used is simple linear regression analysis, correlation analysis, coefficient of determination analysis, and t test. The results of testing the research show that return on equity has a significant influence on stock prices. This result can be seen in the correlation analysis (r) of 0.82 which means that the relationship is very strong. The results of the coefficient of determination analysis show that return on equity has an influence on stock prices of 67.24% and 32.76% influenced by other factors not examined. The constant value of this regression equation is positive. This shows that the dependent variable Y will increase constantly if the variable X is zero. While the value of 15.752.67 shows that if the variable X (Return On Equity) is ignored then the stock price will be worth a 15.752.67 from b of 653,812.04 indicating that each increase in the variable Return on Equity (ROE) of 1 unit will be followed by a share price increase of 2, 40935758%. Whereas partially t test because t count <t table is 2.03 <4.30 then Ho is accepted and Ha is rejected meaning there is no effect due to the fluctuating financial conditions.